Ecuador : Poverty Assessment - World Bank (Washington, DC, 2013)
Ecuador's poor economic performance is not solely nor mainly the result of high volatility, but rather the result of poor economic management and, especially, weak productivity growth. This connection between productivity and economic growth has become even more relevant in recent years, after Ecuador decided to adopt the US dollar as the national currency in 2000, hence forgoing the option of using exchange rate policy to generate temporary increases in competitiveness and growth. Although the decision to dollarize undoubtedly improved the investment climate, reassured potential investors and hence, potentially increased the capacity of the economy to create employment and reduce poverty, sustained increases in productivity will be required to maintain positive growth rates and declining poverty rates in the future. As a consequence, the focus of this report is on productivity growth and its effect on employment, income and, most importantly, poverty. The report pays special attention to the relationship between poverty and the productive sectors, both from a macroeconomic and a microeconomic point of view, and both in urban and rural areas. In following this approach, it not only complements the previous Ecuador Poverty Assessment (World Bank, 2000c), which focused mainly on poverty and social services, but also provides important insights regarding the relationship between economic growth, productivity and employment generation on the one hand, and poverty reduction on the other. Moreover, in thinking about poverty, the report concentrates on monetary, rather than on non- monetary aspects of well-being, since it is the former that appears to be more intimately linked to the evolution of GDP and productivity growth and, hence, has exhibited little improvement over the past years - namely, while social outcomes and access to basic services in Ecuador have improved slowly but continuously since 1980, the national consumption-based poverty rate increased from 40 to 45 percent between 1990 and 2001, as discussed below, with much larger increases in urban areas. . Finally, the report makes use of a variety of sources, both quantitative and qualitative, as well as of existing work in order to provide policy recommendations that will help Ecuador and its government design an effective poverty reduction strategy based on economic and productivity growth.